Aspidistra averyanovii and A. parviflora (Asparagaceae), two new species Central Vietnam - Lý, Ngọc-Sâm; Tillich, Hans- Juergen (Phytotaxa, 2016)
Two new species of Aspidistra, A. averyanovii and A. parviflora from Central Vietnam, Quảng Ngãi Province, are described, including assessment of conservation status and comparison to most similar congeners.